Promotional strategy to enhance the brand awareness of Alibaba Door & Furniture - Afreen, Sadia (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.